Granting Employee Stock Options (ESOs), Market Reaction and Financial Performance - Obiyathulla Ismath Bacha; Sharifah Raihan Syed Mohd Zain; Mohd Eskandar Shah Mohd Rasid; Azhar Mohamad (Asian Academy of Management Journal of Accounting and Finance, 2009)
This paper examines several issues related to the implementation of ESOs among Malaysian companies. We examine a total of 52 companies, 26 ESO firms and their matched industry peers over a span of 12 years. We find ESO firm stocks to have marginally higher mean returns and lower volatility than do their pre-ESO peers. Malaysian companies are more likely to initiate ESOs when the market valuation of their stocks is low. If there is any timing, ESO initiation is timed to be most favourable to employee recipients. Market reaction to ESO announcements is significantly negative. Furthermore, stock prices do not seem to recover to pre-announcement levels during at least the subsequent 20 trading days or one calendar month. In line with US findings, operating performance deteriorates for ESO companies. Comparative analysis of control firms rules out industry or external factors as elements of the deterioration. Firm size has been identified in previous studies as a determinant of market reaction and post-ESO performance. Indeed we find this to be the case for Malaysian ESOs. We find a positive announcement effect for large firms but a significantly negative one for small firms. Though puzzling, the market reaction makes sense when we consider the poor operating performance post-ESO of small firms relative to large ones. It appears that the impact of an ESO is negative for small firms but neutral for large ones. The market appears to anticipate this outcome and react accordingly. An ESO realigns the interest of the stakeholders of a company. Employee recipients gain, while shareholders mostly lose. Bondholders of large ESO firms are only marginally affected, but those of small firms stand to lose from the diminution of profits and increased leverage post-ESO. Based on our results, it will be difficult to make a case that the objectives of and rationale for an ESO are being fulfilled.